A neo-institutional perspective on ethical decision-making - Chan, C.; Ananthram, Subra (Springer New York LLC, 2018)
Drawing on neo-institutional theory, this study aims to discern the poorly understood ethical challenges confronted by senior executives in Indian multinational corporations and identify the strategies that they utilize to overcome them. We conducted in-depth interviews with 40 senior executives in Indian multinational corporations to illustrate these challenges and strategies. By embedding our research in contextually relevant characteristics that embody the Indian environment, we identify several institutional- and managerial-level challenges faced by executives. The institutional-level challenges are interpreted as regulative, normative and cognitive shortcomings. We recommend a concerted effort at the institutional and managerial levels by identifying relevant strategies for ethical decision-making. Moreover, we proffer a multi-level model of ethical decision-making and discuss our theoretical contributions and practical implications.